Mental Health and Work-Life Balance as A Moderating Variable the Influence of Social Media on Employee Performance - Vinno Petrus Manoppo; Gde Bayu Surya Parwita; Debiyanti Kune; Kohar; Hilarius Wandan (Yayasan Inovasi Kemajuan Intelektual, 2023)
This study aims to investigate the complex dynamics between social media usage and employee performance within the modern corporate landscape of 2026. Specifically, it examines the role of Mental Health and Work-Life Balance (WLB) as dual moderating variables that can either mitigate or exacerbate the impact of digital connectivity on professional productivity. Utilizing a quantitative approach with a sample of 500 corporate employees, the research explores how the pervasive nature of social media-often characterized by information overload and social comparison-affects task completion and focus. The conceptual framework integrates the Job Demands-Resources (JD-R) model and Social Cognitive Theory to map these relationships. Preliminary findings suggest that while social media can facilitate networking and information sharing, its influence on performance is highly contingent upon an individual's psychological state and their ability to maintain boundaries between professional and personal life. Mental health acts as a critical filter; employees with high psychological resilience can leverage digital tools more effectively, whereas those with compromised mental health experience increased burnout. Furthermore, work-life balance serves as a second-tier moderator, where a healthy balance attenuates the negative